The Influence of Brand and Promotion on Increasing Sales in Medan Sadis Coffee - Sinaga, Febriani Br.; Sitanggang, HD. Melva; Silaen, Karina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine Brand and Promotion on Sales Increase, this research uses quantitative methods with an associative approach. In this study, the population of consumers who come to Medan Sadis Coffee. The sampling method in this study used a probability sampling technique using a random sampling method of 92 respondents. Data analysis techniques used validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F test, and coefficient of determination (R2) using SPSS version 16. The results of the t-test for the brand variable are t count -1.665 < t table is 1.986, meaning that the brand variable has no significant effect on increasing sales and the promotion variable t count is 4.220 > t table is 1.986 meaning that the promotion variable has a significant effect on increasing sales. F test of brand and promotion variables Fcount of 9.189 > F table 3.10 means that brands and promotions simultaneously affect sales increase.